2022
DOI: 10.55563/clinexprheumatol/tz9i6y
|View full text |Cite
|
Sign up to set email alerts
|

Blood transcriptome and machine learning identified the crosstalk between COVID-19 and fibromyalgia: a preliminary study

Abstract: ObjectiveThe COVID-19 pandemic caused by SARS-CoV-2 has seriously threatened the human health. Growing evidence shows that COVID-19 patients who recovery will persist with symptoms of fibromyalgia (FM). However, the common molecular mechanism between COVID-19 and FM remains unclear. MethodsWe obtained blood transcriptome data of COVID-19 (GSE177477) and FM (GSE67311) patients from GEO database, respectively. Subsequently, we applied Limma, GSEA, Wikipathway, KEGG, GO, and machine learning analysis to confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It was, therefore, hypothesized that these cytokines are a key mediator of pain in patients with FM. Other genes identified in the study and related to post-COVID FM were related to leukotriene synthesis, activation of innate immunity, and oxidoreductive stress [ 138 , 139 ].…”
Section: The Role Of Pathogensmentioning
confidence: 99%
“…It was, therefore, hypothesized that these cytokines are a key mediator of pain in patients with FM. Other genes identified in the study and related to post-COVID FM were related to leukotriene synthesis, activation of innate immunity, and oxidoreductive stress [ 138 , 139 ].…”
Section: The Role Of Pathogensmentioning
confidence: 99%
“…Increased research has shown that patients with COVID-19 have several immunological abnormalities that resemble those of autoimmune diseases (6,7). SARS-CoV-2 infection can cause chronic inflammatory and immune responses that not only directly mediate tissue damage but may also induce serious sequelae of autoimmune disease in susceptible populations (8)(9)(10). With the increasing number of people recovering from SARS-CoV-2 infection, the connection between COVID-19 and autoimmune diseases is gaining significance.…”
Section: Introductionmentioning
confidence: 99%
“…In their article published in the current issue of Clinical and Experimental Rheumatology, Zhang et al published an interesting paper investigating the molecular mechanisms underlying the connection between COVID-19 and fibromyalgia (FM) (1), a connection that has recently been explored even more deeply in the literature (2). Using blood transcriptome data from COVID-19 and FM patients, the authors employed a variety of analysis techniques, including Limma, GSEA, Wikipathway, KEGG, GO, and machine learning analysis, to identify common pathogenesis and key genes for the diagnosis of COVID-19 related FM.…”
mentioning
confidence: 99%